The impact of a multi-level maternal health programme on facility delivery and capacity for emergency obstetric care in Zambia. Issue 10 (3rd October 2018) - Henry, Elizabeth G.; Thea, Donald M.; Hamer, Davidson H.; DeJong, William; Musokotwane, Kebby; Chibwe, Kenneth; Biemba, Godfrey; Semrau, Katherine
ABSTRACT: In 2012, Saving Mothers, Giving Life (SMGL), a multi-level health systems initiative, launched in Kalomo District, Zambia, to address persistent challenges in reducing maternal mortality. We assessed the impact of the programme from 2012 to 2013 using a quasi-experimental study with both household- and health facility-level data collected before and after implementation in both intervention and comparison areas. A total of 21, 680 women and 75 non-hospital health centres were included in the study. Using the difference-in-differences method, multivariate logistic regression, and run charts, rates of facility-based birth (FBB) and delivery with a skilled birth provider were compared between intervention and comparison sites. Facility capacity to provide emergency obstetric and newborn care was also assessed before and during implementation in both study areas. There was a 45% increase in the odds of FBB after the programme was implemented in Kalomo relative to comparison districts, but there was a limited measurable change in supply-side indicators of intrapartum maternity care. Most facility-level changes related to an increase in capacity for newborn care. As SMGL and similar programmes are scaled-up and replicated, our results underscore the need to ensure that the health services supply is in balance with improved demand to achieve maximal reductions in maternal mortality.